2010
DOI: 10.1253/circj.cj-09-0714
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Electrocardiogram-Gated Axial 64-Detector Computed Tomographic Angiography vs Retrospective Gated Helical Technique to Assess Coronary Artery Bypass Graft Anastomosis: - Comparison of Image Quality and Patient Radiation Dose -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp ultidetector computed tomographic (CT) coronary angiography is used widely to detect coronary artery disease (CAD) because it is accurate and noninvasive. The novel application of the angiographic view has currently improved the clinical feasibility, especially for explaining disease distribution and severity to the patient and for discussing the treatment strategy in conference. 1-3 Single-center studies have rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
1
18
2
Order By: Relevance
“…Until now, there are only two studies [15,16] for evaluation of bypass graft by using CCTA with PGTtechnique. Chazen et al [15] suggested PGT technique should be used whenever ventricular functional assessment is not required, and Machida et al [16] reported 64-MDCT with PGT-technique is even superior with RGH-technique in limiting the radiation dose and maintaining the image quality for the assessment of distal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, there are only two studies [15,16] for evaluation of bypass graft by using CCTA with PGTtechnique. Chazen et al [15] suggested PGT technique should be used whenever ventricular functional assessment is not required, and Machida et al [16] reported 64-MDCT with PGT-technique is even superior with RGH-technique in limiting the radiation dose and maintaining the image quality for the assessment of distal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chazen et al [15] suggested PGT technique should be used whenever ventricular functional assessment is not required, and Machida et al [16] reported 64-MDCT with PGT-technique is even superior with RGH-technique in limiting the radiation dose and maintaining the image quality for the assessment of distal anastomosis. However, they did not study the diagnostic accuracy of the PGT- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were excluded from the analysis as they either focused on the assessment of coronary stenting or coronary bypass instead of coronary artery disease [38][39][40].…”
Section: General Informationmentioning
confidence: 99%
“…18 Our hypothesis was that state-of-the-art MDCT would be able to detect changes in the coronary artery as does quantitative coronary angiography, but in a non-invasive manner with a low radiation burden. Thus, our aim was to verify the feasibility of a non-invasive MDCT technique of assessing endothelial vasomotor function, as compared with MBF quantitation using PET/CT.…”
Section: Editorial P 45mentioning
confidence: 99%